2015
DOI: 10.1007/s11096-015-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors that affect adverse drug reaction reporting among hospital pharmacists in Western China

Abstract: Higher professional title, having received training, mastering knowledge about reporting, and being a clinical pharmacist were positive predictors of pharmacist-led adverse drug reaction reporting. Lack of access to reporting forms was a negative predictor. Continuous training and establishing incentive mechanisms are needed to promote adverse drug reaction reporting among hospital pharmacists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…Study done among pharmacists in Western China also showed that higher professional title was an important determinant of knowledge and attitude of pharmacists. 24 However in our study, it did not translate into ADR reporting practices as none of the BSc nurses had ever reported an ADR. This points to need for more training and motivation.…”
Section: Discussionmentioning
confidence: 68%
“…Study done among pharmacists in Western China also showed that higher professional title was an important determinant of knowledge and attitude of pharmacists. 24 However in our study, it did not translate into ADR reporting practices as none of the BSc nurses had ever reported an ADR. This points to need for more training and motivation.…”
Section: Discussionmentioning
confidence: 68%
“…The number of pharmacist respondents in the eligible studies ranged from 10 to 1870 with a median of 179 (25th percentile = 87.8; 75th percentile = 331.25). Response rate ranges from as low as 10.5% to more than 90% . Most of the studies included in this review surveyed pharmacists working in hospital settings (either alone (27 studies) or with pharmacists working in community settings (19 studies)).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies included in this review lacked a theoretical framework. In papers in which a theoretical framework was utilized, Inmans’ seven deadly sins for not reporting ADEs; Knowledge‐Attitude‐Practice Model (KAP); and theory of planned behaviour were the most frequently used theories to understand pharmacists' reporting of ADEs …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations